An international society and journal for equity in health: 10 years on - Furler, John (2011)
June 2010 marked the 10th Anniversary of the foundation meeting of the International Society for Equity in Health (ISEqH). The formation of the Society was a bold statement, with ambitions to be a global body "to promote equity in health and health services internationally through education, research, publication, communication and charitable support"[1]. The Society particularly aimed to be an organisation that facilitated research on how better to understand and address inequities in health. The main activities of the Society have been a series of biannual conferences as well as the establishment of the International Journal for Equity in Health, the official (but independent) publication of the Society. This paper sets out to record some of the milestones of the Society drawing on the reflections of key researchers who attended the conferences as well as others. The history of the Society will help shape its future and how it responds to important issues facing all interested in global efforts to address continuing and unacceptable inequities in health.